Анализ и исследование схемы разворачивания ключей шифра «Калина» - Дырявый, B. C. (ХНУРЭ, 2009)
This work is devoted to research and analysis of key expansion scheme of symmetric block cipher “Kalina” proposed as a candidate to a national standard of Ukraine. Statistic properties of “Kalina” 128 bit version were tested by NIST STS. Collision properties were researched on reduced versions of the cipher. Important facts and assumptions were received.